Color Changes in Chili (Capsicum frutescens L.) During Thin-Layer Drying - Musdalifah, Nuzlul; Muhidong, Junaedi; Supratomo, Supratomo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study investigates the effects of hot water blanching and air velocity on the color stability of chilli (Capsicum frutescens L.) during thin-layer drying. The objective was to determine optimal pre-treatment and drying conditions that preserve visual quality and enhance drying efficiency. A controlled laboratory-scale dryer was used, applying blanching at 90°C for 3 minutes and air velocities of 1.0 m/s and 1.5 m/s. Color parameters (L*, a*, b*), total color change (?E*), and hue angle shift (?H*) were measured periodically. Statistical analysis was conducted using ANOVA and Tukey HSD tests. The results show that blanching significantly improved color retention and reduced enzymatic browning. Higher air velocity accelerated drying and enhanced uniformity, with the combination of blanching and 1.5 m/s airflow yielding the best outcomes in terms of color stability and drying time. Interaction effects between blanching and airflow were synergistic, contributing to improved product quality. These findings align with previous studies and reinforce the importance of integrated drying strategies. In conclusion, the study demonstrates that combining blanching with optimized airflow enhances drying kinetics and preserves the visual quality of chili. These insights are valuable for small-scale processors and contribute to the development of efficient postharvest technologies. Future research should explore nutrient retention, aroma profiles, and advanced modeling of drying behavior. Contribution to Sustainable Development Goals (SDGs):SDG2: Zero HungerSDG 4: Quality EducationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production